Effectiveness of Using Imitation Technique Through English Video Towards Students’ English Pronunciation Ability - Khaliatun Mardiyah; Ana Santika (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study was to find out whether learning English using imitation video technique can improve the English pronunciation ability of class X high school students who were divided into 2 groups, namely the experimental group and the control group. This study used a samples of 50 students taken from 25 students the experimental classÂ and 25 students from the control class. In this study, the researcher used student records to determine the pre-test and post-test. Furthermore, the results of the two tests were tested statistically using the normality test, homogeneity test, and t-test. The average value in the data shows that the pre-test value in the class that received treatment was 46.24 and the average value in the post-test was 72.88. after being applied to imitate English videos, there was an increase in the average score of students by 26.64. then the results of the t-test showed to t-table with a significant level of 5% was 2.93 and the degrees of freedom (df) were 48, for the t-test score was 3.61. As the t-test value is greater than the t-table value, Ho is rejected and Ha is accepted. In measuring the level of effect size with d= 1.78 this shows that this study hasÂ strong effective in improving students; English pronunciation skills. Therefore, to improve English pronunciation skills, it is highly recommended to use the technique of imitating English videos through YouTube media.